Influence of Indocyanine Green on Hepatic Gd-EOB-DTPA Uptake: A Proof-of-Concept Study in Mice. Issue 7 (July 2017) - Akai, Hiroyuki; Yasaka, Koichiro; Nojima, Masanori; Inoue, Yusuke; Ohtomo, Kuni; Kiryu, Shigeru
Abstract : Objectives: The aim of this study was to explore the influence of indocyanine green (ICG) on hepatic uptake of gadolinium ethoxybenzyldiethylenetriaminepenta-acetic acid (Gd-EOB-DTPA). Materials and Methods: Groups of 6 female C57BL6 mice were injected with 5 mg/kg ICG, 20 mg/kg ICG, or phosphate-buffered saline (control group) 10 minutes before the injection of Gd-EOB-DTPA; identical 3-dimensional gradient echo T1-weighted images were subsequently obtained to create time-intensity curves and to measure the peak contrast ratios (CRs) of liver parenchyma. We studied both hypothermic and normothermic mice. Peak CRs for all experimental conditions were evaluated, and among-group differences were assessed using 2-way factorial analysis of variance with Bonferroni post hoc testing. Results: In hypothermic mice, the time-intensity curves of the 3 groups gradually increased from 5 to 30 minutes and almost plateaued after 30 minutes. The peak CR decreased as the amount of injected ICG increased (control group, 5 mg/kg ICG, 20 mg/kg ICG: 1.66 ± 0.09, 1.37 ± 0.18, 1.25 ± 0.24, respectively). In normothermic animals, the time-intensity curves of the control and ICG 5 mg/kg groups peaked 10 to 15 minutes after injection, the peak CRs were very similar (control group, 5 mg/kg ICG: 2.01 ± 0.16, 1.95 ± 0.14, respectively), and the intensities thereof then gradually fell until 60 minutes. Compared with these groups, the ICG 20 mg/kg group exhibited lower peak CR (1.48 ± 0.14) and a weaker decrease in intensity to 60 minutes. Both the amount of ICG injected ( P < 0.001) and the experimental temperature ( P < 0.001) significantly affected the measurements. Conclusions: Indocyanine green inhibits the hepatic uptake of Gd-EOB-DTPA and affects the signal intensity upon Gd-EOB-DTPA–enhanced magnetic resonance imaging. Such inhibition was more obvious in hypothermic mice.